2011
DOI: 10.1002/ar.21361
|View full text |Cite
|
Sign up to set email alerts
|

Role of CD4+CD25+ Regulatory T Cells in Melatonin‐Mediated Inhibition of Murine Gastric Cancer Cell Growth In Vivo and In Vitro

Abstract: Melatonin is an important immune modulator with antitumor functions, and increased CD4 þ CD25 þ regulatory T cells (Tregs) have been observed in tumor tissues of patients and animal models with gastric cancer. However, the relationship between melatonin and Tregs remains unclear. To explore this potential connection, we performed an in vivo study by inoculating the murine foregastric carcinoma (MFC) cell line in mice and then treated them with different doses of melatonin (0, 25, 50, and 100 mg/kg, i.p.) for 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 69 publications
(50 citation statements)
references
References 31 publications
0
48
0
1
Order By: Relevance
“…A preliminary study has highlighted the in vivo inhibitory actions of melatonin on Treg cell generation in cancer patients[34]. It has been reported that in vivo administration of melatonin to mice subjected to experimental cancer has down regulation of CD4+CD25+ Treg cells and Foxp3 expression in tumor tissues[35]. These results suggest that melatonin may have adjuvant effect in inhibiting colitis associated cancer development in patients with IBD.…”
Section: Discussionmentioning
confidence: 99%
“…A preliminary study has highlighted the in vivo inhibitory actions of melatonin on Treg cell generation in cancer patients[34]. It has been reported that in vivo administration of melatonin to mice subjected to experimental cancer has down regulation of CD4+CD25+ Treg cells and Foxp3 expression in tumor tissues[35]. These results suggest that melatonin may have adjuvant effect in inhibiting colitis associated cancer development in patients with IBD.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, IL-2 is fundamental as a growth factor for T lymphocytes, with these cells playing an essential role in the generation of an effective anticancer immunity. Also, melatonin decreases expression of CD4+ CD25+ regulatory T cells and Foxp3 in tumor tissue [80].…”
Section: Modulation Of the Immune Responsementioning
confidence: 98%
“…So, several experiments were aimed at increasing cytotoxic T cells and decreasing Tregs in tumor tissue. Liu et al (2011) showed that melatonin can reduce Tregs numbers in the tumor tissues of patients and also animal in vivo models with gastric cancer.…”
Section: Effects On T Regulatory (Tregs) Cellsmentioning
confidence: 99%